BAZNAS Kabupaten Gresik dan Strategi Pendekatan Public Relations dalam Peningkatan ZISWAF - Hanadi Sirajuddin Munir Baidowi (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2019)
A good zakat management requires both professional management and socialization. In 2016 the target achieved by BAZNAS Gresik Regency was 5 billion. This number is still small compared to the potential for compulsory zakat in East Java, which is around 15 trillion. If we look more closely, the muzakki in BAZNAS Gresik Regency are mostly civil servants. This is seen in contrast to the vision of BAZNAS zakat socialization which is aimed at increasing public awareness in general, not only for civil servants. The results of this study are: first, the steps taken by BAZNAS in Gresik Regency in increasing the number of muzakki are to approach the local government; second, the Gresik Regency BAZNAS strategy in increasing the number of muzakki, among others, makes Gresik Regency BAZNAS a reckoned organization, as a zakat service center for a populist community; third, prioritizing the public relations approach by optimizing zakat income and generating ziswaf by installing banners, stickers, online zakat websites, social media, as well as by establishing partnerships with a number of electronic media and conducting counseling/audiences.